Different effects of dexmedetomidine and midazolam on the expression of NR2B and GABAA‐α1 following peripheral nerve injury in rats. Issue 2 (17th January 2018) - Chen, Jiayu; Li, Hanjun; Lim, Grewo; McCabe, Michael F.; Zhao, Wei; Yang, Yunli; Ma, Weiqing; Li, Na
Abstract: Neuropathic pain is a complex, chronic pain condition and the treatment is a major clinical challenge. Recent studies have shown that two FDA approved drugs dexmedetomidine (DEX) and midazolam (MZL), may be useful in treating neuropathic pain, but the mechanism is not fully dementated. Here, we investigated the effects and mechanisms of DEX and MZL treatment in the peripheral nerve injury model. Intramuscular injection with DEX and MZL attenuated the development of mechanical allodynia and thermal hyperalgesia in rats with chronic constriction injury (CCI). Concurrently, the expression of NMDA receptor subunit 2B (NR2B), GABA (A) receptor subunit alpha1 (GABAA‐α1), and Sonic Hedgehog (SHH) displayed different temporal patterns in the thalamus and the ipsilateral dorsal horn of the spinal cord after CCI. Such that (1) NR2B expression was decreased on day 1 and 14, whereas GABAA‐α1 expression was increased on day 1 in the thalamus, and NR2B expression was decreased on day 1, whereas GABAA‐α1 expression was increased on day 1 and day 30 in the ipsilateral spinal cord dorsal horn after DEX treatment. (2) NR2B expression was increased on day 1, then decreased on day 14 and returned to baseline on day30, whereas GABAA‐α1 expression was no significant changes on day 1, 14, 30 in the thalamus, and NR2B expression was decreased on day 14 and 30, whereas GABAA‐α1 expression was no changes on day 1 and 14 but increased on day 30 after MZL treatment. Furthermore, the mechanical allodynia was significantly attenuated after PUR administration. Meanwhile the expression of NR2B was significantly decreased, and the expression of GABAA‐α1 was significantly increased, in the thalamus and in the ipsilateral spinal cord dorsal horn when detected on postoperative day 1, 7, and 14. Our findings indicate that DEX and MZL have different mechanisms in CCI rats, suggesting different strategies could be considered in managing neuropathic pain in different individuals. © 2018 IUBMB Life, 70(2):143–152, 2018